2018
DOI: 10.1007/s12282-018-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of circulating T regulatory cell subsets in breast cancer patients

Abstract: Collectively, the current study shows phenotypic alterations in suppressive receptors of Treg subsets, suggesting that breast cancer patients have increased activity of N nTregs, EM nTregs and Tr1 cells; and EM nTregs and CD25 Tr1 cells represent prospective markers for assessing disease prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In line with this, reduced numbers of CD39 + FOXP3 + Tregs were observed in patients affected by multiple sclerosis (MS), indicating that CD39 expression in Tregs is critical in controlling inflammatory autoimmune disorders [ 24 ]. In contrast, circulating levels of CD39 + CD25 + Tregs were elevated in cancer patients [ 47 , 48 ], while their low levels were associated with improved relapse-free survival in melanoma patients [ 49 ]. Accordingly, CD39 + Treg frequency and adenosine-mediated immunosuppression were significantly increased in head and neck patients [ 50 ].…”
Section: Cd39 Expression and Functions In Conventional Cd4 + T Cells And Tregsmentioning
confidence: 99%
“…In line with this, reduced numbers of CD39 + FOXP3 + Tregs were observed in patients affected by multiple sclerosis (MS), indicating that CD39 expression in Tregs is critical in controlling inflammatory autoimmune disorders [ 24 ]. In contrast, circulating levels of CD39 + CD25 + Tregs were elevated in cancer patients [ 47 , 48 ], while their low levels were associated with improved relapse-free survival in melanoma patients [ 49 ]. Accordingly, CD39 + Treg frequency and adenosine-mediated immunosuppression were significantly increased in head and neck patients [ 50 ].…”
Section: Cd39 Expression and Functions In Conventional Cd4 + T Cells And Tregsmentioning
confidence: 99%
“…Interestingly, another retrospective study analyzed the clinical impact of the expression of CTLA-4 by different cells of the TME in BC showing that the group of patients with high CTLA-4 expression on interstitial lymphocytes and with a low CTLA-4 expression on tumor cells had the best outcomes (DFS and OS) [105]. CTLA-4 expression in both tumor cells and TILs was associated with worse DFS and OS in luminal B HER2− BC [106]. A flow cytometry study investigating the intracellular protein expression of CTLA-4 by BC CD4 + TILs revealed its almost low expression in the luminal versus HER2-positive and TNBC subtypes, as a consequence of their lower baseline immune infiltration [107].…”
Section: Ctla-4: a Key Actor In Cancer Immune Evasionmentioning
confidence: 99%
“…Cari et al assessed GITR mRNA expression in 3169 BC patients of all subtypes and found an overexpression in 42% of the cases [31]. Other studies demonstrated that expression is increased in both infiltrating [34] and circulating Tregs of BC patients [35,37]. Interestingly, GITR seems to also be overexpressed in CD4+ T-cells in BC-infiltrated lymph nodes [36] (Table 1).…”
Section: Markers Predominantly Expressed On T-lymphocytesmentioning
confidence: 99%